Biological soil crust salvage for dryland restoration: an opportunity for natural resource restoration. (10th August 2020) - Tucker, Colin; Antoninka, Anita; Day, Natalie; Poff, Boris; Reed, Sasha
Abstract : Biocrusts' functional importance and vulnerability to disturbance have motivated consistent interest in biocrust restoration, as well as a recent increase in research to cultivate biocrusts in laboratory and greenhouse settings for use in ecological restoration. As part of a sustainable approach to developing biocrust restoration, we argue that a complementary step is to improve and accelerate methods for salvaging biocrusts that would otherwise be destroyed in a forthcoming disturbance. The increasing rate and scale of disturbance pressures in drylands where biocrusts flourish means that the supply of salvageable biocrust and demand for that material in restoration greatly exceed the present cultivable supply. In this article we describe the state of knowledge for biocrust salvage, present a simple set of steps for conducting a salvage harvest, discuss risks and benefits when considering using salvage, and suggest future research directions to facilitate scaling up biocrust restoration using salvaged material. A focus on the use of salvaged biocrust as a restoration source may prove an important step to improve ecological restoration in notoriously difficult to restore dryland ecosystems.